Antenna Selection for Decode and Forward Based MIMO Cooperative Networks - Aydin, Erdogan; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2014)
In this paper, a cooperative system structure that utilizes decode and forward (DF) method with antenna selection based on the signal to noise ratio (SNR) have been proposed. In order to decrease performance degradation due to error propagations in DF based wireless cooperative networks and increase the error performance of the system, selection combining (SC), classical maximal ratio combining (MRC), cooperative-maximal ratio combining (C-MRC) and link adaptive regeneration (LAR) techniques have been utilized at destination. Error performance analyses of the considered structures are investigated using optimal decision rules determined theoretically for the corresponding relaying strategy.
Keywords: Cooperative diversity; SNR based selection relaying; error propagation; selection combining; maximal ratio combining; cooperative maximal ratio combining; link adaptive relaying; PERFORMANCE ANALYSIS; DIVERSITY; DEMODULATION; Engineering; Telecommunications